The First Continental Congress : A Step Towards New America's Political Stability - Laib, Nadjiba; Kouidri, Halima Saadia (University of Eloued جامعة الوادي, 2024)
Freedom and independence represent the dream of everyone on the earth .The American colonies marched on these ideals through various means, whether diplomatic or military, to achieve independence and establish a self-reliant nation .In this context, the efforts of the American people against British rule emerged prominently with the First Continental Congress which served a significant milestone in the history of the independence movement. The speeches of the leaders who faced challenges with strong resolve , demonstrated their readiness to sacrifice for the realization of the American people's dream of freedom and achieving their dignity. In fact , through these efforts and sacrifices, they succeeded in rescuing the dream of the American people and achieving independence from British rule. Thus, the flag of freedom now flies high over the United States, under a new unified rule, bearing the motto "Freedom or Death," reflecting the values of the American people and their determination for independence and dignity. تعتبر الحرية حلم كل شخص علي وجه الأرض . وقد سعت المستعمرات الأمريكية بكل الوسائل المتاحة، سواء الدبلوماسية أو العسكرية، لتحقيق الحرية وإقامة مجتمع مستقل بذاته. وفي هذا السياق،تبرز جهود الشعب الأمريكي ضد التاج البريطاني، ومن أبرزها المؤتمر الأول الذي شكّل محطة هامة في تاريخ الثورة الأمريكية من اجل الاستقلال . فقد أثبتت خطابات القادة الذين تحدوا الصعاب واظهروا إصرارهم ، أنهم مستعدون للتضحية من أجل تحقيق حلم الشعب الأمريكي بتحقيق الحرية واستعادة كرامتهم.وبفعل هذه الجهود والتضحيات، تمكنوامن تحقيق حلم الشعب الأمريكي بالاستقلال عن الحكم البريطاني. وبهذا، أصبحت راية الحرية ترفرف في سماء الولايات المتحدة الأمريكية، تحت حكم جديد موحد، وبشعار "الحرية أو الموت" الذي يعكس قيم الشعب الأمريكي وإصراره على نيل الاستقلال.
Literature and Civilization
Keywords: First Continental Congress - Conference Leaders – Freedo; المؤتمر القاري الأول - قادة المؤتمر – الحرية